Endgame in the Balkans : Regime Change, European Style - Pond, Elizabeth (Book collections on Project MUSE., 2006)
Can Europe tame the Balkans? This is the question that veteran journalist Elizabeth Pond poses in her timely and absorbing book. With rich detail and penetrating analysis, Pond first sets the scene of the 1990s' wars of Yugoslav succession and the region's yearning to join the European Union zone of peace and prosperity.